ECCO-ESGAR Topical Review on Optimizing Reporting for Cross-Sectional Imaging in Inflammatory Bowel Disease. (10th October 2021) - Kucharzik, Torsten; Tielbeek, Jeroen; Carter, Dan; Taylor, Stuart A; Tolan, Damian; Wilkens, Rune; Bryant, Robert V; Hoeffel, Christine; De Kock, Isabelle; Maaser, Christian; Maconi, Giovanni; Novak, Kerri; et al.
Abstract: Background and Aims: The diagnosis and follow up of patients with inflammatory bowel disease [IBD] requires cross-sectional imaging modalities, such as intestinal ultrasound [IUS], magnetic resonance imaging [MRI] and computed tomography [CT]. The quality and homogeneity of medical reporting are crucial to ensure effective communication between specialists and to improve patient care. The current topical review addresses optimized reporting requirements for cross-sectional imaging in IBD. Methods: An expert consensus panel consisting of gastroenterologists, radiologists and surgeons convened by the ECCO in collaboration with ESGAR performed a systematic literature review covering the reporting aspects of MRI, CT, IUS, endoanal ultrasonography and transperineal ultrasonography in IBD. Practice position statements were developed utilizing a Delphi methodology incorporating two consecutive rounds. Current practice positions were set when ≥80% of the participants agreed on a recommendation. Results: Twenty-five practice positions were developed, establishing standard terminology for optimal reporting in cross-sectional imaging. Assessment of inflammation, complications and imaging of perianal CD are outlined. The minimum requirements of a standardized report, including a list of essential reporting items, have been defined. Conclusions: This topical review offers practice recommendations to optimize and homogenize reporting in cross-sectional imaging in IBD.